NAFKAH KELUARGA OLEH ISTRI IMPILKASINYA PADA MASYARAKAT TANJUNG BALAI KABUPATEN ASAHAN - Faisar Ananda, Hafsah, Azuratunnasuha, (Program Pascasarjana UIN Sumatera Utara Medan, 2018)
Abstraks : Livelihood is something given by someone to their wives, relatives and property to fulfill their basic needs. The basic needs are in the form of food, clothing and shelter. Family according to Islam is an institution built on the basis of faith in God. Family according to the modern West (feminist) is an institution built on the philosophy of materialism and individualism. The position of women in Islam is very noble, both as mothers, wives and children. Husbands and wives have the same rights and obligations as men in all areas of life. Islam when applied in the family, this institution can survive, the number of divorce is not much, the honor of women is maintained, and their comfort is protected both when it's easy and old. So that it can be concluded that the feminism movement is an awareness to change all forms of injustice, subordination, and marginalization of women, towards a society of harmony between men and women in the shade of the principles of justice and equality in the structure of the system and the structure of society , religious leaders state that it is obligatory to help their husbands in fulfilling family needs is the majority view of the community in Bagan Asahan Baru Village. The view of the first group mentioned, that their knowledge is obligatory to help with family needs if her husband is less able to meet family needs. Even though there were only a few of them, the financial results of an established husband but his wife continued to participate in earning a living for various reasons. The negative impact of career women is closely related to the issue of feminism that is developing in the West. The issue is one of the children born from the post modernime womb. Etymologically the word ‘feminiseme' comes from the Latin word, ‘femina' in English translated ‘femine' which means that it has women's qualities. The word gets the word 'ism', so it becomes an understanding, namely an understanding that carries gender issues related to the fate of women who have not received fair treatment in various sectors of life, both domestic, political, social, economic and educational sectors.